Historical and Contemporary Trends in Spirituality Leadership - Magnusen, Christy L. (Catholic Education: A Journal of Inquiry and Practice, 2003)
A good society relies on the education of its citizenry. Following the 1983 publication of A Nation at Risk (National Commission on Excellence in Education), America turned a skeptical eye toward its educational institutions. Specifically targeting the leadership of its schools, our country called for a closer examination of the characteristics of school administrators and what factors predicted an effective school. Influenced by the parallel findings in business and organizational management, the habits, beliefs, practices, personalities, and styles of leaders were closely assessed for their ability to instill a sense of community and good will in their respective organization. Toward the end of the 20th century, social scientists suggested that effective leadership was more than profit margins, effective offices and power. Revealing a persuasive nexus between leadership and spirituality, theorists such as Parker J. Palmer and others set the stage for a new standard by which leaders would be judged. The morality and integrity of leaders became more important than ever. This essay will explore the concept of spirituality and its influence in leadership throughout history. Although this dimension has been overlooked until recently, it is a critical component to a leader’s effectiveness, particularly in education.